2017
DOI: 10.1136/bcr-2016-218448
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of cylindrical batteries and its management

Abstract: In contrast to the ingestion of coin batteries, the ingestion of cylindrical batteries is an uncommon medical presentation. Owing to their larger size, cylindrical battery ingestion can lead to serious complications including intestinal haemorrhage, bowel obstruction, bowel perforation, peritonitis and even death. We discuss the case of a 17-year-old girl who presented after swallowing three cylindrical batteries. Her medical history included depression and previous battery ingestion that required surgical rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…10,11,13,14,21,22 In 2017, Tien and Tanwar reported a case of a 3-battery ingestion that resulted in gastric ulcers and gastritis within 14 hours, despite the patient denying destruction of the battery cases. 24 Our review of the abdominal x-rays provided with the case suggested distortion of the battery casing that would have explained the gastric find-ings. Two batteries were removed urgently from the stomach; the third had passed to the small bowel.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…10,11,13,14,21,22 In 2017, Tien and Tanwar reported a case of a 3-battery ingestion that resulted in gastric ulcers and gastritis within 14 hours, despite the patient denying destruction of the battery cases. 24 Our review of the abdominal x-rays provided with the case suggested distortion of the battery casing that would have explained the gastric find-ings. Two batteries were removed urgently from the stomach; the third had passed to the small bowel.…”
Section: Discussionmentioning
confidence: 92%
“…We summarize these cases in the Table. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Most reported cases involved patients who were asymptotic after ingestion. If symptoms did occur, they usually manifested as upper GI complaints or abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Button battery and pediatric patients are more commonly observed in the literature, 1 but there are patient groups that have ingested cylindrical AA battery as in our case, although rare. Complications such as perforation 3 and fatal haemorrhage 5 may develop when battery is ingested as a foreign body into the gastrointestinal systems due to its chemical composition. As for battery ingestion, the American Society for Gastrointestinal Endoscopy Guidelines recommend emergency treatment in case of esophageal obstruction, whereas cylindrical batteries should be removed in the event that they remain in the stomach for more than 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…As for battery ingestion, the American Society for Gastrointestinal Endoscopy Guidelines recommend emergency treatment in case of esophageal obstruction, whereas cylindrical batteries should be removed in the event that they remain in the stomach for more than 48 hours. 3,6 This period is indicated as 24 hours for sharp foreign bodies such as nails in the upper gastrointestinal system. 7 In our case, cylindrical AA battery being on constant move in the gastrointestinal system with the lactulose treatment and the reinforcement of this movement with abdominal radiography might have reduced the risk of fatal complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation